Treatment for Intramuscular Lipoma Frequently Confused with Sarcoma: A 6-Year Restrospective Study and Literature Review. (9th December 2014) - Han, Hyun Ho; Choi, Jong Yun; Seo, Bommie F.; Moon, Suk-Ho; Oh, Deuk Young; Ahn, Sang Tae; Rhie, Jong Won
Abstract : Introduction. Intramuscular lipoma is a very rare form of lipoma, known to be categorized as an infiltrating lipoma due to its tendencies to infiltrate the muscle or the synovium. Contrary to other subcutaneous lipomas, even after surgical removal, the rate of local recurrence ranges at a high rate from 50∼80% and differential diagnosis with liposarcoma is very difficult. Patients and Methods. A retrospective chart review was conducted for a total of 27 patients. Before performing a surgery based on the types of mass, a radiologic imaging study was performed. An intraoperative frozen biopsy was performed on every patient and the results were compared. The progress was monitored every 3 to 6 months for recurrence or struggles with rehabilitation. Results. There were 13 male and 14 female patients with an average age of 54.6. The average tumor size was 8.2 cm (1.1 cm∼31.6 cm). Excision was performed using a wide excision. All 27 individuals were initially diagnosed as intramuscular lipoma; however, 1 of the patients was rediagnosed as liposarcoma in the final checkup. The patients had an average of 3 years and 1 month of follow-up and did not suffer recurrences. Conclusion. Thus, it is essential that a frozen biopsy is performed during the surgery in order to identify its malignancy. And a wide excision like malignant tumor operation is a principle of treatment.